2023
DOI: 10.3389/fpsyg.2023.1134094
|View full text |Cite
|
Sign up to set email alerts
|

Implementing psychosocial support models in contexts of extreme adversity: lessons from a process evaluation in Colombia

Arturo Harker Roa,
Natalia Córdoba Flechas,
Andrés Moya
et al.

Abstract: IntroductionHigh quality investments during early childhood allow children to achieve their full potential by setting developmental foundations. However, challenges in the scale-up of evidence-based interventions make across-the-board implementation a non-trivial matter. Moreover, extreme contextual conditions -such as community violence, forced displacement, and poverty- impose a double threat. First, by directly affecting early childhood development (ECD), forced displacement and exposure to violence during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Several clients and providers recognized that the ability to identify with each other strengthened the trust and rapport, thus facilitating engagement and participation. The benefits of training community members as providers and delivering MHPSS in community-based settings have also been observed in other MHPSS studies conducted among refugees and migrants and displaced populations in Latin America [55][56][57]. Community-based MHPSS interventions delivered through task sharing have been tested in multiple refugee settings and has been recommended as a strategy to bridge gaps in the availability, appropriateness, and accessibility of MHPSS in these communities [19].…”
Section: Implications Of Study Findings Related To the Feasibility Ac...mentioning
confidence: 73%
“…Several clients and providers recognized that the ability to identify with each other strengthened the trust and rapport, thus facilitating engagement and participation. The benefits of training community members as providers and delivering MHPSS in community-based settings have also been observed in other MHPSS studies conducted among refugees and migrants and displaced populations in Latin America [55][56][57]. Community-based MHPSS interventions delivered through task sharing have been tested in multiple refugee settings and has been recommended as a strategy to bridge gaps in the availability, appropriateness, and accessibility of MHPSS in these communities [19].…”
Section: Implications Of Study Findings Related To the Feasibility Ac...mentioning
confidence: 73%
“…Few studies have also included host community members as lay providers (Cohen and Yaeger, 2021 ). Many of these studies have identified that the peer- and group-based nature of mental health and psychosocial interventions is a valuable aspect of the intervention format for study participants (Dickson and Bangpan, 2018 ; Cohen and Yaeger, 2021 ; Harker Roa et al, 2023 ). Prior research has also reinforced the centrality of community stakeholder engagement to the successful implementation of mental health and psychosocial support in low-income and humanitarian contexts (Dickson and Bangpan, 2018 ; Greene et al, 2021 ; Harker Roa et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a process evaluation of Semillas de Apego, a psychosocial program for caregivers in Colombia, similarly found that the group format formed and strengthened social support networks. Participants also described that mindful breathing and other relaxation techniques were useful skills to manage stress and promote well-being (Harker Roa et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%